2016
DOI: 10.1002/mpr.1514
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the PTSD screening cartoon test “Darryl” in a Danish clinical sample of children and adolescents

Abstract: The current study examined the reliability and validity of a Danish adaptation of "Darryl", a cartoon-based measure of DSM-IV symptoms of post-traumatic stress disorder (PTSD) in a sample of Danish children and adolescents. Exposure to potentially traumatizing events, PTSD symptoms and diagnostic status were assessed in 65 children between the ages of 7 and 17 years old. Participants were recruited from a crisis centre for battered women and a school for children with emotional and behavioural problems. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The text alongside each cartoon asks about the psychological responses specific to the traumatic experience, in this case, stalking. In a validation study of the Danish version of Darryl, it showed good internal consistency for the overall scale (α = 0.88) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The text alongside each cartoon asks about the psychological responses specific to the traumatic experience, in this case, stalking. In a validation study of the Danish version of Darryl, it showed good internal consistency for the overall scale (α = 0.88) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A cartoon-based measure of symptoms of posttraumatic stress disorder (PTSD) as defined by the Diagnostic and Statistical Manual of Mental Disorders, 4th ed, when self-administered among Danish children and adolescents in high-risk settings correlated with a clinicianadministered PTSD scale for children and adolescents. A receiver operating characteristic analysis suggested that the cartoon-based measure significantly predicted PTSD in this population [39]. The use of an educational comic book on epilepsy resulted in increased knowledge about the cause, treatment, and first response during a seizure among rural and urban Ethiopian high school students [40].…”
Section: Graphic Medicine As a Teaching Toolmentioning
confidence: 93%
“…These data are entered into the DCC system according to whether a given mental health symptom is present (coded as 1) or absent (coded as 0). Depending on the age of the child, different validated and age-appropriate mental health screening and assessment tools are used during the sessions including the Beck Youth Inventories-II of Emotional and Social Impairment (BYI-II; Beck, 2001), the Trauma Symptom Checklist for Children (TSCC; Briere, 1996), the Havard Trauma Questionnaire (HTQ; Mollica et al, 1992), the Diagnostic Infant Preschool Assessment (DIPA; Scheeringa & Haslett, 2010), and a Danish adaptation of the Darryl PTSD screening cartoon test (Løkkegaard et al, 2017;Neugebauer et al, 1999) (The Danish National Board for Social Services, 2019).…”
Section: Methodsmentioning
confidence: 99%